Misja Świętego Jacka na Rusi w świetle tradycji dominikańskiej (Krakowskie Pismo Kresowe, 2009)
The mission of saint Hyacinth in Ruthenia in Dominicans traditionArticle is based on dominicans historiography and many information about saint Hyacinth and his activity in Ruthenia are analysed. Relations of such Dominicans writers like Seweryn from Lubomla, Abraham Bzowski, Szymon Okolski, Klemens Chodykiewicz and Sadok Barącz were used. It is necessary also to recall dispute about division of polish Dominicans province in the beginnings of XVII century and its impact to polish and ruthenians monks points of view. Their opinions about the history of Dominican Order in Ruthenia as well as saint Hyacinth’s activity were different. Some problems from relations concern mission to Ruthenia are particularly important: distance of journey, places visited by saint and events that took place in Kiev and Halicz. These questions, we can find in all relations, show us aims and intentions to modify Hyacinth’s part in Dominicans tradition.